Lateral Flow Assay for the Detection of African Swine Fever Virus Antibodies Using Gold Nanoparticle-Labeled Acid-Treated p72 - Zhu, Wenzhuang; Meng, Kaiwen; Zhang, Yueping; Bu, Zhigao; Zhao, Dongming; Meng, Geng (Frontiers in Chemistry, 2022)
African swine fever is a widespread and highly contagious disease in the porcine population, which is caused by African swine fever virus (ASFV). The PCR and ELISA detection methods are the main conventional diagnostic methods for ASFV antigen/antibody detection in the field. However, these methods have limitations of expensive equipment, trained technicians, and time-consuming results. Thus, a rapid, inexpensive, accurate and on-site detection method is urgently needed. Here we describe a double-antigen-sandwich lateral-flow assay based on gold nanoparticle-conjugated ASFV major capsid protein p72, which can detect ASFV antibody in serum samples with high sensitivity and specificity in 10 min and the results can be determined by naked eyes. A lateral flow assay was established by using yeast-expressed and acid-treated ASFV p72 conjugated with gold nanoparticles, which are synthesized by seeding method. A high coincidence (97.8%) of the assay was determined using clinical serum compared to a commercial ELISA kit. In addition, our lateral flow strip can detect as far as 1:10,000 diluted clinically positive serum for demonstration of high sensitivity. In summary, the assay developed here was shown to be rapid, inexpensive, accurate and highly selective. It represents a reliable method for on-site ASFV antibody detection and may help to control the ASFV pandemic.